A call to action for expanded sleep research in pediatric oncology: A position paper on behalf of the International Psycho‐Oncology Society Pediatrics Special Interest Group. Issue 3 (3rd November 2019) - Daniel, Lauren C.; van Litsenburg, Raphaele R.L.; Rogers, Valerie E.; Zhou, Eric S.; Ellis, Sarah J.; Wakefield, Claire E.; Stremler, Robyn; Walter, Lisa; Crabtree, Valerie McLaughlin; ,
Abstract: Sleep and circadian rhythms are closely related to physical and psychosocial well‐being. However, sleep and circadian rhythm disruptions are often overlooked in children with cancer, as they are frequently considered temporary side effects of therapy that resolve when treatment ends. Yet, evidence from adult oncology suggests a bidirectional relationship wherein cancer and its treatment disrupt sleep and circadian rhythms, which are associated with negative health outcomes such as poor immune functioning and lower survival rates. A growing body of research demonstrates that sleep problems are prevalent among children with cancer and can persist into survivorship. However, medical and psychosocial outcomes of poor sleep and circadian rhythmicity have not been explored in this context. It is essential to increase our understanding because sleep and circadian rhythms are vital components of health and quality of life. In children without cancer, sleep and circadian disturbances respond well to intervention, suggesting that they may also be modifiable in children with cancer. We present this paper as a call to (a) incorporate sleep or circadian rhythm assessment into pediatric cancer clinical trials, (b) address gaps in understanding the bidirectional relationship between sleep or circadian rhythms and health throughout the cancer trajectory, and (c) integrate sleep and circadian science into oncologic treatment.